Hormonal Implications of SARS-CoV-2: A Review of Endocrine Disruptions - Aliya Yskak; Yevgeniy Sokharev; Kuanysh Zhumalynov; Elizaveta Koneva; Natalia Afanasyeva; Dmitri Borodulin; Dmitrii Babaskin; Almabek Nugmanov; Murat Nurushev; Vadim Chashkov (Scientifica)
To improve medical care and rehabilitation algorithms for patients affected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), it is important to evaluate and summarize the available data on the effect of coronavirus infection (COVID-19) on the endocrine system. The purpose of this review was to study the effect of COVID-19 on the endocrine system. The scientific novelty of this study is the evaluation of the effect of coronavirus infection on the endocrine system and the potential effect of hormones on susceptibility to COVID-19. The results of this review show that the endocrine system is vulnerable to disorders caused by COVID-19, mainly thyroid dysfunction and hyperglycemia. The information in the published literature mentioned here contains some unclear aspects and contradictory data, but much remains to be studied and clarified regarding the impact of COVID-19 on the endocrine system. In particular, this concerns the study of the hyperglycemic status of patients who have had coronavirus infection, which is extremely important for the future metabolic health of COVID-19 survivors. This review contributes to the scientific discourse by systematically synthesizing disparate studies to identify patterns, gaps, and emerging trends in the literature concerning the effects of COVID-19 on the endocrine system. By integrating these findings, this study offers a novel perspective on potential hormonal interactions influencing COVID-19 susceptibility and outcomes, proposing new hypotheses and frameworks for future research.